2018
DOI: 10.3389/fmicb.2018.01707
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Characterization of Endophytic Fungi Isolated From the Tropical Mangrove Species, Rhizophora mucronata, and Identification of Potential Antagonists Against the Soil-Borne Fungus, Fusarium solani

Abstract: Rhizophora mucronata is an important ecosystem entity of the Malaysian mangrove forest. Since the species grows in a harsh environment, any organism that is isolated from this species would be of huge interest due to its potential in having novel bioactive compounds. In the present work, we isolated, identified and characterized, a total of 78 fungal isolates harboring inside the leaf tissues of R. mucronata. Molecular identification using the nuclear ribosomal DNA internal transcribe spacer (ITS) sequences re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 79 publications
9
107
0
1
Order By: Relevance
“…Hamzah et al (2018) tested the antimicrobial activity of different endophytic fungi isolated from the Malaysian mangrove Rhizophora mucronata against Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus and found that Fusarium lateritium and Xylaria sp. showed antibacterial activities against the pathogenic bacteria.…”
mentioning
confidence: 99%
“…Hamzah et al (2018) tested the antimicrobial activity of different endophytic fungi isolated from the Malaysian mangrove Rhizophora mucronata against Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus and found that Fusarium lateritium and Xylaria sp. showed antibacterial activities against the pathogenic bacteria.…”
mentioning
confidence: 99%
“…To evaluate inhibitory activity of Humicola sp. JS-0112 against mycelial growth of 10 phytopathogenic fungi and oomycetes (Figure 1), dual culture assay was conducted as previously reported with minor modifications (Hamzah et al, 2018). Fungal disks of JS-0112 and pathogen (5 mm) were co-disposed at 5cm distance on the PDA petri dish for most of the test fungi except Phytophthora species, which used V8 agar medium.…”
Section: Determination Of Antifungal Activity By Dual-culture Assaymentioning
confidence: 99%
“…suggested strong antimicrobial activity against different virulent strains such as E. coli, P. aeruginosa, K. pneumonia, Proteus vulgaris, S. aureus, Bacillus cereus, Streptococcus pyogenes, B. subtilis, P. syringae pv. lachrymans or acid ovorax avenae and anti-mycobacterial activity against Mycobacterium tuberculosis [28][29][30][31][32] . Terrestrial endophytic Fusarium sp.…”
Section: Discussionmentioning
confidence: 99%